ظاهرة القياس وأثرها في النحو العربي - إبراهيم، عبدالله علي محمد (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنين بالديدامون بالشرقية, 2019)
القياس هو الأساس الذي تتسع على الإلمام به لغتنا العربية، وهو واسع المجال مترامي الأطراف يمت إلي كل باب من أبواب العربية بصلة، ويكاد ذكره يجرى عند تحقيق كل مسألة و"سيبويه" إمام النحاة لم يغفل القياس حيث عده مصدرا من مصادر النحو، وتحدث عنه كثيرا في "كتابه"، الذي جاء جامعا لعلم النحو وأصوله مشتملا على أبوابه وفصوله، وجاء العلماء بعد سيبويه فساروا على نهجه من حيث الاهتمام بالأصول النحوية، وخاصة "القياس" فنجد ابن حني" يتحدث عنه كثيرا في كتبه مثل "الخصائص"، والتصريف الملوكي الذي شرحه ابن يعيش، وذكر فيه كثيرا "القياس" شارحا ومعللا لأسبابه. والقياس أنواع قياس على الأصل الذي تتفاوت اللغات فيه جودة وفصاحة وجميعها مما يصح القياس عليه، ولهذا نرى بعض العلماء يصرحون بأن كل ما كان لغة لقبيله صح القياس عليه، وإذا نظرنا إلى النحاة نجد أنهم عندما استقرئوا كلام العرب وجدوه على قسمين: - قسم اشتهر استعماله وكثرت نظائره فجعلوه قياسا مطردا - وقسم لم يظهر فيه وجه القياس لقلته، وكثرة ما يخالفه فوصفوه بالشذوذ، ووقفوه على السماع لأنه غير فصيح. وهناك قياس التمثيل، والمراد به الحاق نوع من الكلم بنوع آخر في حكم، وهو ما ينكره بعض النحاة ويعنونه بقولهم إن اللغة لا تثبت بالقياس. أما قياس الشبه: فهو قياس بعض أنواع الكلم على بعض، إذا انعقد بينهما شبه من جهة المعني أو من جهة اللفظ. أما قياس العلة: فيقصد به وجود علة بين الأصل والفرع، وهو أنواع تحدثت عنها بالتفصيل. أما قياس التمثيل: فقد ذكرت فيه أن قياس التمثيل يكون صحيحا ويتم الاستدلال به على تقرير حكم من أحكام اللفظ متى كان وجه الشبه بين الأصل والفرع واضحا، وقد بينت في هذا البحث أسباب الاختلاف في القياس، ومن أسباب اختلافهم في صحة القياس أن يتوفر لدي العالم من استقراء كلام العرب ما يكفي لتركيب القاعدة فيجيز القياس عليها، ولا يبلغ الآخر بتتبعه مقدار ما يؤخذ منه حكم كلي، فيقصر الأمر على السماع، وقد يستوي الفريقان أو يتقاربان فيما عرفوه من الشواهد، ويكتفي به أحدهما في فتح باب القياس ويستقله الآخر فلا يتخطى به حد السماع. ومن أسباب اختلافهم في القياس اختلاف نظائرهم في الشاهد أو الشواهد التي تذكر ليقاس عليها واختلافهم في أمانه ناقلها أو في صحة عربية قائلها فإذا فقدت الثقة في ناقلها أو في فصاحته لا يكون لكلامه وزنا، ولا يعتمد عليه في شيء من أحكام اللسان. وقد توصلت لعدة نتائج من أهمها: - أن ما جعله العرب قليلا يحفظ ولا يقاس عليه، قد يرد به القرآن الكريم فيصير قويا يصح القياس عليه كما ورد في حذف "أن" المصدرية. - أن لغات العرب تتفاوت في الجودة والفصاحة وجميعها مما يصح القياس عليه - أن سيبويه اكتفى باللفظ الواحد الذي ورد سماعا في لغة واحدة وجوز القياس عليه مثل النسب إلى كلمة "شنوءة". - الأكثر في السماع هو الأرجح في الاستعمال لأنه مألوف عند المخاطبين أكثر من الوجه الذي قل في السماع وإن كان أرجح من جهة القياس.
Measurement is the basis, upon which our Arabic language can be understood, and it is broad in scope and sprawling, which pertains to every chapter of the Arabic link, and it is almost mentioned that it is carried out upon the investigation of every issue. Much has been found in his “book”, which came to be a synthesis of grammar and its origins, including its chapters and chapters, and scholars came after Sibueh, so they followed his approach in terms of interest in grammatical origins, especially “analogy” so we find “Ibn Jana” he talks about a lot in his books such as “characteristics” and conjugation The king, who was explained by Ibn Yaish, and mentioned in it a lot of "measurement", explaining and explaining his reasons. And the measurement is types of measurement on the original, in which the languages differ in quality and eloquence, and all of them are valid for the analogy, and this is why we see some scholars say that everything that was a language for the tribe is true to the analogy, and if we look at grammarians we find that when they read the words of the Arabs they found it in two parts: - A department famous for its use and its many counterparts, making it a steady measurement - And a section in which the analogy of his lack of appearance did not appear, and there was a lot of contradiction to it, and they described it as an anomaly, and they stood on it because it was not eloquent. There is a measurement of representation, and it is intended to attach one type of speech to another type of judgment, which is what some grammarians deny and mean by saying that language is not proven by analogy. As for the measurement of similarities: it is the measurement of some types of speaking to each other, if a similar contract was held between them on the one hand or the word. As for the measurement of illness: it means the existence of a problem between the origin and the branch, which are the types that I talked about in detail. As for the measurement of representation: I mentioned in it that the measurement of representation is correct and it is inferred to determine a ruling from the provisions of the word when the similarity between the original and the branch is clear, and I have indicated in this research the reasons for the difference in measurement, and among the reasons for their difference in the validity of the measurement that the world has Whoever extrapolates the words of the Arabs is enough to install the rule, and it is permissible to measure it, and not inform the other by following the amount of what is taken from a total judgment, so the matter is limited to hearing, and the two sides may equal or converge with what they knew from the evidence, and one of them suffices to open the door of the measurement and the other is independent, so it does not exceed it Hearing limit. Among the reasons for their difference in analogy is the difference of their counterparts in the witness or evidence that are mentioned to be measured, and their difference in the safety of its carrier or in the health of an Arab who said that if you lose confidence in its vector or in its eloquence, its words do not have weight, and it does not depend on it in any of the provisions of the tongue. - What made the Arabs a little preserved and not measured by it, the Holy Qur’an might return it, and it will become strong and it is correct to measure it, as stated in the omission of “An”. - The languages of the Arabs vary in quality and eloquence, all of which is correct to measure - Sibuyeh was satisfied with the one word that was heard in one language, and it is permissible to measure it, such as the lineage to the word “shanwa”. The most common in hearing is more likely to be used because it is more familiar to the two addressees than to the face that is less heard, even if it is more likely in terms of measurement.
Keywords: النحو العربي -- اللغة العربية -- ظاهرة القياس